Tau PET imaging predicts cognition in atypical variants of Alzheimer's disease. Issue 2 (6th November 2017) - Phillips, Jeffrey S.; Das, Sandhitsu R.; McMillan, Corey T.; Irwin, David J.; Roll, Emily E.; Da Re, Fulvio; Nasrallah, Ilya M.; Wolk, David A.; Grossman, Murray
Abstract: Accumulation of paired helical filament tau contributes to neurodegeneration in Alzheimer's disease (AD). 18 F‐flortaucipir is a positron emission tomography (PET) radioligand sensitive to tau in AD, but its clinical utility will depend in part on its ability to predict cognitive symptoms in diverse dementia phenotypes associated with selective, regional uptake. We examined associations between 18 F‐flortaucipir and cognition in 14 mildly‐impaired patients (12 with cerebrospinal fluid analytes consistent with AD pathology) who had amnestic ( n = 5) and non‐amnestic AD syndromes, including posterior cortical atrophy (PCA, n = 5) and logopenic‐variant primary progressive aphasia (lvPPA, n = 4). Amnestic AD patients had deficits in memory; lvPPA in language; and both amnestic AD and PCA patients in visuospatial function. Associations with cognition were tested using sparse regression and compared to associations in anatomical regions‐of‐interest (ROIs). 18 F‐flortaucipir uptake was expected to show regionally‐specific correlations with each domain. In multivariate analyses, uptake was elevated in neocortical areas specifically associated with amnestic and non‐amnestic syndromes. Uptake in left anterior superior temporal gyrus accounted for 67% of the variance in language performance. Uptake in right lingual gyrus predicted 85% of the variance in visuospatial performance. Memory was predicted by uptake in right fusiform gyrus and cuneus as well as a cluster comprising right anterior hippocampus and amygdala; this eigenvector explained 57% of the variance in patients' scores. These results provide converging evidence for associations between 18 F‐flortaucipir uptake, tau pathology, and patients' cognitive symptoms.